“I now go to church, I am not under the chief” - Timo Kallinen (Suomen Antropologi, 2008)
Today traditional chieftaincy in Africa has become a topic of public and academic discussions about good governance, democracy, civil society and the like. Chieftaincy is perceived increasingly as a ‘political institution’ and the religious quality of the chiefly offices that the classic ethnographies emphasized has been largely forgotten. The essay seeks to explain this disjuncture by looking at the case of the Asante people of Ghana, claiming that one of the most dramatic changes brought by the colonial rule was the secularization of indigenous leadership, which permanently transformed the ways in which the traditional institutions were conceptualized. The origin of the contemporary ‘political discourse’ about chiefs is traced to the conflicts between Christian missions and chiefs during the early colonial period.